Mapping evidence on access to healthcare information by women of reproductive age in low-and-middle-income countries: scoping review protocol - Shatilwe, Joyce T. (Syst Rev, 2019)
BACKGROUND: Research shows that there are inadequate interventions in resource-limited settings that could enable women of reproductive age to access and use health services in those settings. The main objective of this scoping review is to map the evidence on access to healthcare information by women of reproductive age in LMICs. METHOD AND ANALYSIS: The primary search will include Google Scholar, Science Direct, PubMed, EBSCOhost (Academic search complete, CINAHL with full text, MEDLINE with full text, MEDLINE), Emerald, Embase, CDSR, PsycINFO, published and peer review journals, organisational projects, conference papers, reference list, grey literature sources, as well as reports related to this objective will be included in the study. Identified keywords will be used to search articles from the studies. The articles and abstracts will be screened by two independent reviewers (JS and TPMT). Inclusion and exclusion criteria will be considered to guide the screening. A thematic content analysis will be used to present the narrative account of the reviews, using NVivo computer software (version 11). DISCUSSIONS: The scoping review will focus on women of reproductive age in LMICs. We anticipate finding relevant literature on the interventions aimed at accessing health care services in LMICs. The study findings will help reveal research gaps to guide future research. SCOPING REVIEW REGISTRATION: Not registered with PROSPERO (not needed). PROTOCOL AND REGISTRATION: This scoping review was not registered.